UTILIZATION OF SOCIAL MEDIA AND DIGITAL ADVERTISING TO INCREASE SALES: UTILIZATION OF SOCIAL MEDIA AND DIGITAL ADVERTISING TO INCREASE SALES - Muin, Mulyani Rody; Erdawati, Erdawati (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
This community service project aimed to enhance the sales performance of PT Dirgham Art Jaya, a furniture manufacturing SME in Sidoarjo, by implementing integrated digital strategies through social media management and digital advertising. The initiative responded to the company’s minimal digital presence and reliance on word of mouth promotion, which limited brand visibility and market reach. Activities included creating official business accounts on Instagram and TikTok under the handle “sahabatdirgham,” producing engaging visual content with CapCut and Canva, launching targeted advertisements via TikTok Ads and Instagram Ads, and registering the business location on Google Maps. Audience segmentation focused on demographics and interests relevant to home décor and furniture. The program achieved notable outcomes, including increased followers, content views, and customer orders from 5 in May to 8 in June indicating a positive correlation between optimized digital marketing and sales growth. The results highlight the potential of consistent content management, data driven advertising, and multi channel engagement to enhance SME competitiveness. Sustainability recommendations involve continuous performance monitoring, advanced analytics training, and diversification of content formats to ensure long term digital growth and adaptability in the competitive creative industry.